PENGARUH THIN CAPITALIZATION, SIZE DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK - indriyani; Siarwi (Jurnal Nusa Akuntansi, 2025)
This research was conducted to determine the effect of Thin Capitalization, Size and Capital Intensity on Tax Aggressiveness. The sample used in this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2018- 2022 period. The sampling technique used in this research was the purposive sampling method. The population of this research is all manufacturing companies with a population of 22 companies and a sample of 17 companies. The research method used is secondary data. Hypothesis testing was carried out using the panel data regression method using a fixed effect regression model and assistance from E-views 12 software. The results of this research show that thin capitalization and capital intensity have no effect on tax aggressiveness, while size has an effect on tax aggressiveness. Simultaneously thin capitalization, size and capital intensity influence tax aggressiveness.